Correlation Between ST-Segment Elevation in Lead aVR and Severity of Left Main Coronary Artery Stenosis in Acute Coronary Syndrome Patients (Community Based Medical Journal, 2026)
Incidence of acute coronary syndrome (ACS) is increasing day by day. ECG is the first line method to diagnose ACS. ST-segment elevation or depression determines the presence or absence of IHD or STEMI / NSTEMI. Augmented limbs leads are used, aVR, aVF and aVL to obtain information from heart. Often lead aVR is ignored; ST-segment elevation in aVR may determine left main coronary artery stenosis (LMCAS). A cross-sectional study was conducted in the Department of Cardiology, Punjab Institute of Cardiology, Lahore, Pakistan, from June 2015 to July 2016, to determine the correlation between ST-segment elevation in lead aVR and severity of LMCA stenosis on angiography in ACS patients. A total of 60 patients with acute coronary syndrome with ST-segment elevation in lead aVR undergoing angiography were included through non-probability, purposive sampling. The mean age was 56.13±9.56 years. There were 53(88.33%) males and 7(11.67%) females; male-female ratio was 7.57:1. There were 27(45%) patients with diabetes mellitus, 39 (65%) patients had hypertension, 5(8.3%) patients had hyperlipidemia and 25 (41.67%) were smokers. There were 31(51.7%) patients who had V1 1mm and 29(48.3%) had V1 2mm. The mean value of aVRST was 1.08±0.54 mm. LMCAS was found in 25(41.7%) cases, while 14 cases had 0.5mm aVRST, there was only one case who had LMCAS. out of 43 cases who had 1-2mm aVRST, 21 had LMCAS and among 3 cases of aVRST 2-3mm, all had significant LMCAS detected on angiography (p